2019
DOI: 10.1039/c9fo01443h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of secondary heat-induced aggregation on pork meat batter protein conformation, hydration characteristics, textural quality and in vitro digestibility

Abstract: SH has caused fierce aggregation and the conformation transition from α-helix to β-sheets, which resulted in the decrease of WHC, textural quality and in vitro digestibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 40 publications
3
9
0
Order By: Relevance
“…In addition, protein digestibility is related to its secondary structure . The lower protein digestibility in BO and RO samples is consistent with previous studies, which reported that more β-sheet structure resulted in lower protein digestibility. , Furthermore, the oxidation of lysine and arginine disrupts the recognition of digestive enzymes with their cleavage sites, thereby reducing the protein digestibility . Based on the protein profile observed by SDS-PAGE (Figure ) and decreased α-helix (Figure ), it could be speculated that unfolding was the main phenomenon in samples treated with SV.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…In addition, protein digestibility is related to its secondary structure . The lower protein digestibility in BO and RO samples is consistent with previous studies, which reported that more β-sheet structure resulted in lower protein digestibility. , Furthermore, the oxidation of lysine and arginine disrupts the recognition of digestive enzymes with their cleavage sites, thereby reducing the protein digestibility . Based on the protein profile observed by SDS-PAGE (Figure ) and decreased α-helix (Figure ), it could be speculated that unfolding was the main phenomenon in samples treated with SV.…”
Section: Resultssupporting
confidence: 87%
“…The higher degree of protein aggregation should be partially responsible for the reduction of DH in BO and RO samples . In addition, protein digestibility is related to its secondary structure . The lower protein digestibility in BO and RO samples is consistent with previous studies, which reported that more β-sheet structure resulted in lower protein digestibility. , Furthermore, the oxidation of lysine and arginine disrupts the recognition of digestive enzymes with their cleavage sites, thereby reducing the protein digestibility .…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Though both α-helices and β-sheets are ordered structures, β-sheets generally represent a more compact and aggregated structure with intramolecular hydrogen bonding (Tan et al, 2021). Moreover, as α-helices are often positively correlated with protein digestibility (Bai et al, 2016;Han et al, 2019), this difference in the secondary structure of myosin between the two muscles can also contribute to digestive characteristics.…”
Section: Secondary Structure Of Myosin In Chicken Breast and Thigh Mu...mentioning
confidence: 99%
“…The protein‐rich materials provided essential amino acids for the human body (Boland et al ., 2013). The nutritious and portable emulsified meat products have favoured by consumers because the finely emulsified meat products contain essential amino acids and a high value of biological protein (Han et al., 2019a,b; Zheng et al ., 2019; Zheng et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%